Scalable Synthesis of dispersible semiconducting metal chalcogenides nanocrystals and their application - Bera, A. (CSIR-NCL, 2021)
The work incorporated in this thesis is mainly focused on various single source metal precursors like metal thiolates and metal dithiocarbamate complexes. Herein, several simple and general methods have been developed for the synthesis of various such single source metal precursors, which comprising the main two constituents of metal chalcogenide nanocrystals (NCs), namely, the tiny inorganic metal chalcogenide complex as core and an organic molecule as shell. Specially, both binary metal thiolates and bimetallic (ternary) thiolates have been prepared and both of them turned out to be excellent precursors for the synthesis of metal sulfide/selenide NCs. The methods used to prepare metal chalcogenide NCs included a direct-heating (solvo-thermal decomposition) method or solid state grinding method. First, the large scale synthesis of various 2D molecular precursors like metal thiolates and metal dithiocarbamate complexes (M-C8DTCA) have been developed and studied their thermal decomposition to metal sulfide NCs via solution based methods. We observed that some of the metal thiolates like Pb-thiolate requires very high temperature to decompose into PbS resulting in particles bigger than their Bohr exciton radius and hence displayed poor optical properties. In the next, to reduce the decomposition temperature an active sulfur precursor called octyl ammonium octyldithiocarbamate (C8DTCA) has been utilized for the synthesis of various metal sulfide NCs (including most challenging PbS NCs, with tunable optical properties) by solution based method (hot injection) or solid state grinding method. We also show that the size of the nanocrystals could be controlled by changing the reaction temperature or metal: chalcogenide precursor ratio. Interestingly, we have also been successful in establishing that these newly developed solid state grinding methods are scalable without compromising their structural and optical properties. The binary or ternary materials synthesized by these solid state routes could be re-dispersed as desired in non-polar organic solvents allowing them to be solution processible. The optical properties of the metal chalcogenide nanocrystals could further be improved by post synthetic surface passivation.
Abhijit Bera_Ph.D thesis
Keywords: Nanocrystals, quantum dots, single source precursor, metal thiolates, C8DTCA, mixed metal thiolates.